OCA/OCP : - Dawes, Chip (Sybex, 2002)
Here's the book you need to prepare for Exam 1Z0-007: Introduction to Oracle9i: In-depth coverage of official exam objectives Practical information on using SQL in a real-world Oracle9i en Hundreds of challenging review questions, in the book and on the CD